Analisis Keterkaitan antara Jumlah Uang Beredar dan PDB Riil Indonesia (Periode 2010.1-2018.12) - Rachman Falitho Alam; Banatul Hayati; Fuad Mas’ud (Universitas Diponegoro, 2020)
Classical economists believe money doesn’t matter or money is neutral, meanwhile keynesian argued that money matter or money isn't neutral. The main purpose of this research is to analyze the linkages between the money supply, such as M0, M1, M2 and real Indonesia’s GDP in a period of 2010.1 to 2018.12. Data processed using the (Vector Error Correction Model) method. The results have shown that M0, M1, and M2 have a significant effect to real GDP. Impulse response analysis shows the response of real GDP tend to be positive to real GDP shock itself, M0 and M2, meanwhile the shock of M1 have negative response. The shock happened to real GDP partially contributed by the real GDP itself, and followed by M0, M1, and M2. In conclusion, along the period of 2010 to 2018, neutrality of money phenomenon are not happening in Indonesia. The implication is to maintain the stability of real GDP in Indonesia by focusing on monetary policy to control the money supply such as M0, M1 and M2.